Design and fabrication of portable trolley garbage collector - Irwan, Irdina Qistina (2023)
The limits of traditional vacuum cleaners are highlighted in this abstract, and a portable trolley rubbish collector is suggested as a potential improvement. Although vacuums can be used for a variety of cleaning tasks, they are mostly surface-level cleaners and may need additional cleaning methods for the best results. Cleaning damp surfaces can be difficult, and dust bags could get hurt. Additionally, because of the smaller diameter of the vacuum nozzle, vacuum cleaners are limited in their ability to suction bigger debris. In order to address these problems, the proposed portable trolley garbage collector offers enough capacity to hold a variety of rubbish, including solid waste and small debris. Because of the trolley's simple mobility design, it may be used in a variety of locations, including homes, public spaces, and construction sites. This technology encourages hygiene and environmental sustainability by increasing rubbish collection efficiency. The project's goals are to decrease energy use in garbage management and create a hoover trolley that can successfully suction heavier particles